Genetic diversity in threatened plant species Alnus nitida (Spach.) Endel - Khan, Muhammad Khalil Ullah; Muhammad, Noor; Uddin, Nisar; Ali, Niaz; Umer, Muhammad; Ullah, Shariat (Plant Science Today, 2020)
Alnus nitida (Spach) Endl. is an ethnobotanically important threatened plant species. The genetic diversity among the 50 different genotypes of Alnus nitida was carried out using sodium dodecyl sulfate poly acrylamide gel electrophoresis (SDS-PAGE) characterization. A considerable amount of genetic diversity (90%) was observed among the genotypes of A. nitida. The protein characterization was carried out on 12% gel electrophoresis. A total of 10 protein bands were detected in A. nitida genotypes. SDS-PAGE procedure is a useful method for the investigation of both genetic diversity and phylogenetic relationship. Especially, B-5 was monomorphic in A. nitida genotypes and was considered as species specific. All other bands/loci were polymorphic. These polymorphic bands displayed 12, 16, 72, 88, 2, 44, 84, 54 and 12 percent variation respectively. In the present examination, the high intra-specific diversity was observed representing SDS-PAGE is a powerful tool for determining the genetically diverse germplasms in A. nitida. The results obtained by this study could be helpful in the identification and selection of desired genotypes of Alnus nitida for conservation programmes in future. Today, there is still a need to assess genetic variation and protect genetic resources, especially of wild species for prospective benefits in plant conservation programmes.